2018
DOI: 10.1016/j.anorl.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of allergic rhinitis in Parakou, Benin: Prevalence, severity and associated factors

Abstract: The prevalence of AR symptoms in Parakou was high. A non-negligible proportion of symptoms were severe. This disease merits special attention in the city.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
3
0
1
Order By: Relevance
“…Air pollution has been shown to be one of the major environmental risk factors for allergic rhinitis [31]. A workplace near a high traffic road is also associated with allergic rhinitis [27] as found in our study. The fine particles, mostly derived from road traffic, are ultrafine size (<100 nm) and can be deposited in the nasal and peripheric airways.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Air pollution has been shown to be one of the major environmental risk factors for allergic rhinitis [31]. A workplace near a high traffic road is also associated with allergic rhinitis [27] as found in our study. The fine particles, mostly derived from road traffic, are ultrafine size (<100 nm) and can be deposited in the nasal and peripheric airways.…”
Section: Discussionsupporting
confidence: 72%
“…The prevalence of allergic rhinitis reported in this study is close to that reported (43.6%) in adults who are highly exposed to air pollution from road traffic in Sweden [17]. The prevalence of allergic rhinitis in this study is high compared to that reported in Bogota (26.1%) in traffic police [26] and in a study done in Benin [27] among residents near busy roads with a prevalence of allergic rhinitis of 35.7%. Studies have shown higher prevalence of allergic rhinitis than those found in our study in workers with high exposure to outdoor air pollution in Nigeria (48.9%) [28] and Italy (48.5%) [29].…”
Section: Discussionmentioning
confidence: 44%
“…A total of 24 of the indoor air pollution research articles described exposure to dust. For example, dust was noted as a trigger for allergic rhinitis (Adegbiji et al, 2018) and house dust/dust mite exposure was associated with asthma (Bardei et al, 2016;Flatin et al, 2018). Particulate matter was evaluated in 24 of the indoor air pollution research studies, most focusing on PM10 (Abou-Khadra, 2013;Ibhafidon et al, 2014;Makamure et al, 2016;Jafta et al, 2017;Nkhama et al, 2017;Nkosi et al, 2017;Mentz et al, 2018) and PM2.5 exposures (Oluwole et al, 2013;Chafe et al, 2014;Ibhafidon et al, 2014;Dutta et al, 2017;Lacey et al, 2017;Lin et al, 2017a;Malley et al, 2017;Nkhama et al, 2017;Wylie et al, 2017a;Wylie et al, 2017b;Mentz et al, 2018).…”
Section: Exposures Measuredmentioning
confidence: 99%
“…For example, an incremental life-time cancer risk was considered low in the context of exposure to PAHs from air pollution among city center residents of Kumasi, Ghana (Bortey-Sam et al, 2015). Additional outcomes evaluated included markers of oxidative stress, inflammatory cytokines, and chemokines (Cachon et al, 2014), chronic bronchitis from occupational exposures to dust (Hinson et al, 2016), elevated prostate specific antigen (PSA) among young men exposed occupationally to quarry pollutants (Ewenighi et al, 2017), chronic respiratory symptoms among limestone factory workers in Zambia (Bwalya et al, 2011), and allergic rhinitis in urban areas (Flatin et al, 2018). Exacerbation of silicosis due to higher doses of particulate matter exposure, impacts of exposure to prenatal air pollution on DNA methylation in the context of HIV status and antiretroviral treatment (Goodrich et al, 2016), asthma and asthma exacerbations, mortality, cerebrovascular outcomes, cardiovascular outcomes, and daily respiratory mortality were also evaluated.…”
Section: Health Outcomesmentioning
confidence: 99%
“…Le diagnostic d'une allergie aux acariens requiert la pratique d'explorations telles que les pricks tests, visant à mettre en évidence une sensibilisation de l'organisme vis-à-vis de certaines protéines de l'acarien [5]. Malheureusement, dans nos pays en développement, ces tests sont ne sont pas effectués en routine, faute de matériels ; ce qui contraste avec les fréquentes plaintes de déclenchement des symptômes par la poussière de maison par de nombreux malades [11]. Le diagnostic est par conséquent presque toujours présomptif, avec les risques évidents d'erreurs diagnostiques.…”
Section: Introductionunclassified